2023
DOI: 10.3390/tropicalmed8050278
|View full text |Cite
|
Sign up to set email alerts
|

Putative Contribution of 8-Aminoquinolines to Preventing Recrudescence of Malaria

Abstract: Enhanced therapeutic efficacy achieved in treating Plasmodium vivax malaria with an 8-aminoquinoline (8-AQ) drug such as primaquine (PQ) together with a partner drug such as chloroquine (CQ) is usually explained as CQ inhibiting asexual parasites in the bloodstream and PQ acting against liver stages. However, PQ’s contribution, if any, to inactivating non-circulating, extra-hepatic asexual forms, which make up the bulk of the parasite biomass in chronic P. vivax infections, remains unclear. In this opinion art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…The repellent advised comprises 20-35% N,N-Diethyl-meta-toluamide (DEET). If you are going to be outside at night, wear long-sleeved apparel and long pants [47,48].…”
Section: Preventionmentioning
confidence: 99%
“…The repellent advised comprises 20-35% N,N-Diethyl-meta-toluamide (DEET). If you are going to be outside at night, wear long-sleeved apparel and long pants [47,48].…”
Section: Preventionmentioning
confidence: 99%
“…Later in evolution, further adaptation for prolonged persistence in the liver before fresh blood stage infection (‘long latency phenotype’) may have enabled the parasite to survive in temperate areas with shorter mosquito transmission seasons [ 14 ]. In addition to relapse infections resulting from hypnozoite activation, it has been suggested that P. vivax parasites accumulating in the spleen and bone marrow may serve as an important reservoir that might be the source of recrudescence, contributing to chronic malaria [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%